A simple GIS data for tree management in Universiti Putra Malaysia's arboretum - Jusoff, Kamaruzaman; Setiawan, Iwan (Universiti Putra Malaysia Press, 2002)
Tree location and tree attributes are valuable elements of municipal tree management systems. By creating the tree data in Geographic Information System, users have access to other digital data that can be used in conjunction with tree database. A study was conducted at the Universiti Putra Malaysia's arboretum with an objective to establish a computerized information system for Universiti Putra Malaysia's arboretum. Information about tree position and their attributes information (tree dimension) for 434 trees in arboretum area can be easily retrieved from a simple Geographic Information System database. The GIS database can cope just as easily with other parameters besides species and location. As for routine management, it is only a small step to complement standard tree measurements, with data of a useful, subjective kind, such as that used to record tree condition or management action from existing measurement, perhaps to predict growth, timber yields and even landscape impact. The total area of study site is about 5.7 ha. Family distribution from the area consisted of 12 families, 19 genus and 15 species. Hopea odorata was the highest number of the tree species present with diameter distribution ranging from 4.2 cm to 65.7 cm. About 75 trees inside the area were found dead due to water logging and improper drainage. Labeling or painting of trees should be done in order to monitor their growth, mortality and future tree stand measurement.